Effect of Growth Pressure on Structural Properties of SiC Film Grown on Insulator by Utilizing Graphene as a Buffer Layer - Astuti, Budi; Abd Rahman, Shaharin Fadzli; Tanikawa, Masahiro; Mahmood, Mohamad Rusop; Yasui, Kanji; Manaf Hashim, Abdul (Faculty of Science and Technology, State Islamic University Walisongo Central Java, 2015)
Heteroepitaxial growth of silicon carbide (SiC) on graphene/SiO2/Si substrates was carried out using a home-made hot-mesh chemical vapor deposition (HM-CVD) apparatus. Monomethylsilane (MMS) was used as single source gas while hydrogen (H2) as carrier gas. The substrate temperature, tungsten mesh temperature, H2 flow rate and distance between mesh and substrate were fixed at 750 Â°C, 1700 Â°C, 100 sccm and 30 mm, respectively. The growth pressures were set to 1.2, 1.8 and 2.4 Torr. The growth of 3C-SiC (111) on graphene/SiO2/Si were confirmed by the observation of Î¸-2Î¸ diffraction peak at 35.68Â°. The diffraction peak of thin film on graphene/SiO2/Si substrate at pressure growth is 1.8 Torr is relatively more intense and sharper than thin film grown at pressure growth 1.2 and 2.4 Torr, thus indicates that the quality of grown film at 1.8 Torr is better. The sharp and strong peak at 33Â° was observed on the all film grown, that peak was attributed Si(200) nanocrystal. The reason why Si (200) nanocrystal layer is formed is not understood. In principle, it canât be denied that the low quality of the grown thin film is influenced by the capability of our home-made apparatus. However, we believe that the quality can be further increased by the improvement of apparatus design. As a conclusion, the growth pressures around 1.8 Torr seems to be the best pressures for the growth of heteroepitaxial 3C-SiC thin film.